(untitled) (Minerva, 2019)
In the author’s opinion the highly controversial έρέτησιν in Apollonius Rhodius’Argonautica 11 467 can be only explained as a stylistic election. The poet uses he re a lyric level of language, probably connected with the weight which the choral lyric place s on the noun.